Effect of a Preoperative Preparation Program on Anxiety in School-age Children Undergoing Surgery Using a Factorial Design - Maliheh Shoja; Fatemeh Heshmati Nabavi; Monir Ramezani; Azadeh Saki (Mashhad University of Medical Sciences, 2018)
Background: Surgery is a stressful experience in children. Therefore, the familiarization of this population with treatment processes by means of appropriate training tools and techniques can be an effective way to control their anxiety. Aim: The aim of this study was to determine the effect of a preoperative preparation program on anxiety in school-age children undergoing surgery using a factorial design. Method: This clinical trial was conducted on 81 children aged 6-12 years as candidates for elective surgery at Doctor Sheikh Hospital in Mashhad, Iran, in 2016. A preparation program was implemented with two methods (i.e., displaying video tutorials with and without nurses' explanations) and on two different days (i.e., prior to and on the day of operation) using a factorial design. The estimation of children's anxiety was accomplished by using the Revised Children's Manifest Anxiety Scale administered before training and prior to operating room admission. The data were analyzed by statistical tests in SPSS software, version 16. Results: The study groups were comparable in terms of demographic characteristics (P>0.05). There was no significant differences among the four groups regarding manifest anxiety based on the place of referral (i.e., department or clinic) (P=0.22), presentation or non-presentation of explanations by nurses (P=0.12), and their interaction effects (P=0.22). Implications for Practice: No significant difference was observed among the four groups in terms of manifest anxiety. Therefore, all four training methods were effective in reducing anxiety in children. Consequently, each of these methods can be used depending on human resources and infrastructure of each department.